Rationality of Antibiotic Use in Upper Respiratory Tract Infections in Primary Care - Reza Ahda Kadir (Punggawa Global Research: Jurnal Multidisiplin, 2026)
Upper respiratory tract infections frequently led to antibiotic prescribing in primary care despite the predominance of self-limited viral illness, creating avoidable adverse effects and contributing to antimicrobial resistance. This article examined how rational antibiotic use could be implemented for upper respiratory tract infection syndromes in outpatient first-contact care. A narrative literature review was conducted using secondary sources from recent peer-reviewed research and relevant clinical guidance, and findings were synthesized through qualitative thematic analysis. The review found that antibiotics were justified only in a limited subset of presentations, particularly high-probability or confirmed streptococcal pharyngitis, acute bacterial rhinosinusitis defined by characteristic time-course patterns, and selected acute otitis media meeting diagnostic and severity criteria. In contrast, routine prescribing for viral syndromes, broad-spectrum selection without indication, and unnecessarily prolonged courses represented common forms of inappropriate use. Practical stewardship strategies that reduced unnecessary prescribing included syndrome-specific decision algorithms, structured communication with safety-netting, delayed prescribing in defined uncertainty zones, and routine audit with feedback. These findings supported a targeted approach that aligned clinical decision-making with patient safety and long-term antibiotic effectiveness.